Formation of energy policy in Europe, taking into account trends in the global market. (February 2020) - Provornaya, I.V.; Filimonova, I.V.; Eder, L.V.; Nemov, V.Y.; Zemnukhova, E.A.
Abstract: The article highlights the main trends in the development of world energy. The method of forecasting energy consumption is presented, taking into account the level and dynamics of energy consumption in general, as well as the use of individual energy resources with differentiation by countries and regions. In the present study, when forming the energy forecast, the key indicators determining the global energy demand are the dynamics of the energy intensity of GDP and per capita energy consumption. It is shown that in the total volume of world consumption of primary energy resources, oil will continue to occupy a leading position. Among fossil fuels, the demand for natural gas will increase most intensively. The share of coal in the structure of consumption of primary energy carriers will decrease, which is associated with the replacement of coal with natural gas in order to reduce carbon dioxide emissions. The greatest growth rates of demand among non-fossil fuels will be observed in renewable energy sources. The main growth in atomic energy consumption will be in the developing countries of the Asia-Pacific Region.